Efficacy of Topical Steroidal Treatment and Hand-Care Modification in Chronic Paronychia: A Retrospective Study - Galili, Eran; Shemer, Avner; Magal, Lee; Lyakhovitsky , Anna; Kassem, Riad; Kaplan , Baruch (Dermatology Practical & Conceptual, 2026)
Introduction: Chronic paronychia is a persistent inflammatory condition of the periungual tissue, often triggered by excessive hand exposure to irritants. Despite its high prevalence, treatment remains challenging, with conflicting evidence on the role of microbial colonization, particularly Candida spp., and the efficacy of antifungal and antibiotic therapies. Objectives: To assess the efficacy of topical corticosteroids combined with hand-care modifications and antimicrobial treatments in managing chronic fingernail paronychia. Methods: This retrospective study included 97 patients (mean age 54.3 ±10.6 years, 67% female) with chronic fingernail paronychia (mean disease duration 13.3 ±6.1 years). Patients initially received antifungal and/or antibacterial therapy, followed by corticosteroid-based treatment and strict hand-care modifications. Results: Microbial cultures identified Candida spp. in 95.9% and bacteria in 36.1% of cases. First-line antifungal and/or antibiotic therapy was largely ineffective (76.3% nonresponders). In contrast, second-line corticosteroid-based therapy (mean duration 4.0 ±0.7 months) led to improvement in 90.7% of cases, with 38.1% achieving complete or near-complete resolution. Hand-care modifications included minimizing prolonged contact with liquids, wearing non-powdered waterproof gloves for wet tasks, using mild fragrance-free cleansers, and applying moisturizer after handwashing. Treatment adherence, including these behavioral modifications (P<0.01) and regular topical application (P<0.001) as well as longer treatment duration (P<0.05), were significantly associated with improved outcome. Conclusions: Chronic paronychia is primarily inflammatory, with limited response to antifungals or antibiotics. Prolonged corticosteroid-based therapy combined with hand-care modifications is highly effective, emphasizing the critical role of adherence to achieving clinical improvement.